Déficit em transações correntes, movimentos de capital e ataques especulativos: uma abordagem estruturalista das recentes crises cambiais na América Latina - Curado, Marcelo; Porcile, Gabriel (Estudos Econômicos (São Paulo), 2004)
This work aims to develop a theoretical model of the role that structural deficit in current account, as well as a limited capacity of absorption of financial capital, play in exchange rate crisis in developing countries. The model is specifically framed in the light of the experience of exchange rate crisis in Latin America, especially that of Brazil (1999) and Mexico (1994). The model includes key features of the Latin American economies which have been neglected or taken into account only partially in the current literature on external crisis. In particular, it is argued that recent speculative attacks on some Latin American currencies are related - along with the financial aspects usually highlighted by the existing literature - to competitiveness and technological development.